Spectroscopic characterization of cellulose acetate polymer membranes containing Cu(1,3-butadiene) OTf as a facilitated olefin transport carrier - Kim, HS; Kim, YJ; Kim, JJ; Lee, SD; Kang, YS; Chin, CS (AMER CHEMICAL SOC, 2001)
Polymer-metal complexes composed of Cu(1,3-butadiene)OTf and cellulose acetate (CA), Cu-CA, have been successfully applied to facilitated olefin transport membranes for the olefin/paraffin separation, and the reversible solid-state interactions of Cu+ ions with cellulose acetate (CA) and olefins have been observed using FT-IR and UV spectroscopy. FT-IR study clearly shows that the Cu+ ions in the Cu-CA membrane are coordinated by the carbonyl groups of CA. Upon incorporation of Cut 1,3-butadiene)OTf into CA, the carbonyl stretching frequency of CA at 1753 cm(-1) shifts to a lower frequency at around 1702 cm(-1) and the degree of coordination increases with increasing amounts of Cu(l,3-butadiene)OTf. The Cu+-carbonyl interaction is found to be significantly affected by the coordination of an olefin, suggesting that the olefin and carbonyl group compete with each other for the coordination to Cu+ ions. Reversible olefin coordination to Cu+ ions in the Cu-CA membranes has been observed by FT-IR and UV studies. Treatment of the Cu-CA membrane with propylene, ethylene, or 1,3-butadiene produces a corresponding olefin-coordinated membrane in which the coordinated olefin is easily replaced by another olefin.
Keywords: COMPLEX MEMBRANES; SILVER SALTS; SEPARATION; PROPYLENE; KINETICS; DRY